2015
DOI: 10.18097/pbmc20156103373
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines neuroinflammatory reaction to the action of homoaggregatic and liposomal forms of b-amyloid 1-40 in rats

Abstract: An injection model of preclinical stages of Alzheimer's disease has been reproduced in rats. It was accompanied by the decrease in the latent period of conditioned reflex avoidance, increasing levels of endogenous b-amyloid peptide 1-40 and activation of inflammatory cytokines (IL-1b, TNF-a, IL-6, IL-10) in the cerebral cortex, hippocampus and blood serum of experimental animals. We belive that changes identified at the biochemical level are prerequisite to modulate neuronal functions in rats induced by Ab40_H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…However, in the cerebral cortex of these rats activation of inflammation reaction was also featured, albeit to a lesser extent. This result confirms our previous research, in which it was shown that homoaggregates of Аβ40_Human introduction into the cerebral cortex of rats causes more cytokine response in that part of the brain of rats in comparison with the situation in hippocampus [74].…”
Section: Cytokines Changes In Chronic Neuroinflammation Induced Homoasupporting
confidence: 92%
“…However, in the cerebral cortex of these rats activation of inflammation reaction was also featured, albeit to a lesser extent. This result confirms our previous research, in which it was shown that homoaggregates of Аβ40_Human introduction into the cerebral cortex of rats causes more cytokine response in that part of the brain of rats in comparison with the situation in hippocampus [74].…”
Section: Cytokines Changes In Chronic Neuroinflammation Induced Homoasupporting
confidence: 92%
“…Yet recent studies have demonstrated trophic [9] properties of AβPP (antimicrobial, in particular), that served as basis for its comparison with other antimicrobial peptides (defensins, histatins, and cathelicidins) and attribution to brain's innate immune system [10]. We have proved [11] the role of chronic inflammation in initiation of amyloidosis, and the involvement of cytokines and Aβ in inflammatory response to toxic effects of Aβ-aggregates.…”
Section: Abstract: Curcumin β-Amyloid Peptides 40 and 42 (Aβ mentioning
confidence: 90%